On the Structure and Source of Individual Differences in Toddlers' Comprehension of Transitive Sentences - Donnelly, Seamus; Kidd, Evan (Frontiers in Psychology, 2021)
How children learn grammar is one of the most fundamental questions in cognitive science. Two theoretical accounts, namely, the Early Abstraction and Usage-Based accounts, propose competing answers to this question. To compare the predictions of these accounts, we tested the comprehension of 92 24-month old children of transitive sentences with novel verbs (e.g., “The boy is gorping the girl!”) with the Intermodal Preferential Looking (IMPL) task. We found very little evidence that children looked to the target video at above-chance levels. Using mixed and mixture models, we tested the predictions the two accounts make about: (i) the structure of individual differences in the IMPL task and (ii) the relationship between vocabulary knowledge, lexical processing, and performance in the IMPL task. However, the results did not strongly support either of the two accounts. The implications for theories on language acquisition and for tasks developed for examining individual differences are discussed.